A meta-analysis of antecedents and outcomes of psychological capital in hospitality and tourism - Yan, Zhen; Zhang, Zonggguo; Choo, Wei Chong (Informa UK Limited, 2024)
While numerous studies have explored psychological capital (PsyCap), there has been a limited endeavor to offer a comprehensive overview of PsyCap within the realm of hospitality and tourism. This study conducted a meta-analytical review, seeking to elucidate the direction and magnitude of effect sizes pertaining to the relationships between PsyCap, its antecedents and outcomes, while also considering the moderating effects of national culture, measurement and time lag. To test the proposed hypotheses, altogether, 68 empirical studies (21 antecedents and outcomes, total sample size N = 22,071) were collected and utilized. The results demonstrated that PsyCap had significant associations with antecedents such as leaderships and organizational context and outcomes including work attitudes, emotional labor, role conflicts and stressors, organizational contexts, performance, wellness and life satisfaction and intention to stay or leave. The findings also highlighted the moderating effects of national culture, measurement and time lag on the relationships between PsyCap and its outcomes. To our knowledge, this is the first meta-analysis of PsyCap in the context of hospitality and tourism. In addition, the current research adds value by examining various moderators, which has not been done in previous review articles of PsyCap.